2016
DOI: 10.3109/13880209.2015.1129546
|View full text |Cite
|
Sign up to set email alerts
|

Low concentration of formononetin stimulates the proliferation of nasopharyngeal carcinoma cell line CNE2 by upregulating bcl-2 and p-ERK1/2 expression

Abstract: Context Formononetin is a typical phytoestrogen, which is a bioactive component found in red clover plants. Previous studies have shown that formononetin inhibits the proliferation of several types of cancer cells, including prostate cancer and osteosarcoma. However, how formononetin affects the proliferation of CNE2 is not clear. Objective The objective of this study is to investigate the effects of formononetin on nasopharyngeal carcinoma cells in vitro, along with the underlying mechanism. Materials and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…It inactivates signaling pathways, namely, JAK/STAT pathway, PI3K/AKT pathway, as well as MAPK (ERK1/2) pathways. Formononetin also modulates several miRNA expressions as well as supresses cell migration, invasion, and angiogenesis (Li et al, 2014; Liu et al, 2014b; Yang et al, 2014; Hu and Xiao, 2015; Guo et al, 2016; Qi et al, 2016; Wu et al, 2017; Kim et al, 2018a; Park et al, 2018; Wang et al, 2018; Zhang et al, 2018a). NAG-1, nonsteroidal anti-inflammatory drug (NSAID)-activated gene-1; IAP, inhibitors of apoptosis proteins; IL-6, interleukin-6; PARP, poly(ADP-ribose) polymerase; GSH, glutathione; GSSG, oxidized glutathione; GR, glutathione reductase; PTEN, phosphatase and tensin; HIFα, hypoxia inducible factor α; miR, microRNA; TIMP, tissue inhibitors of metalloproteinases; ER, estrogen receptor; MMP, matrix metalloproteinases; CDK, cyclin dependent kinases; STAT, signal transducer and activator of transcription; PI3K, phosphatidylinositol 3-kinase; AKT, protein kinase B; VEGF, vascular endothelial growth factor; FGF, fibroblast growth factor; FGFR, fibroblast growth factor receptor; IGF-1R, insulin-like growth factor 1 receptor; ERK, extracellular signal-regulated kinase; JAK, Janus kinase; ROS, reactive oxygen species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It inactivates signaling pathways, namely, JAK/STAT pathway, PI3K/AKT pathway, as well as MAPK (ERK1/2) pathways. Formononetin also modulates several miRNA expressions as well as supresses cell migration, invasion, and angiogenesis (Li et al, 2014; Liu et al, 2014b; Yang et al, 2014; Hu and Xiao, 2015; Guo et al, 2016; Qi et al, 2016; Wu et al, 2017; Kim et al, 2018a; Park et al, 2018; Wang et al, 2018; Zhang et al, 2018a). NAG-1, nonsteroidal anti-inflammatory drug (NSAID)-activated gene-1; IAP, inhibitors of apoptosis proteins; IL-6, interleukin-6; PARP, poly(ADP-ribose) polymerase; GSH, glutathione; GSSG, oxidized glutathione; GR, glutathione reductase; PTEN, phosphatase and tensin; HIFα, hypoxia inducible factor α; miR, microRNA; TIMP, tissue inhibitors of metalloproteinases; ER, estrogen receptor; MMP, matrix metalloproteinases; CDK, cyclin dependent kinases; STAT, signal transducer and activator of transcription; PI3K, phosphatidylinositol 3-kinase; AKT, protein kinase B; VEGF, vascular endothelial growth factor; FGF, fibroblast growth factor; FGFR, fibroblast growth factor receptor; IGF-1R, insulin-like growth factor 1 receptor; ERK, extracellular signal-regulated kinase; JAK, Janus kinase; ROS, reactive oxygen species.…”
Section: Resultsmentioning
confidence: 99%
“…Although most studies demonstrated the anticancer effect of formononetin, there were two studies suggesting a potential cancer-promoting effect of formononetin at low concentration (<6 μM). Formononetin was reported to stimulate proliferation of nasopharyngeal CNE2 cells at 0.3 μM by activating ERK1/2 signaling pathway and upregulation of Bcl-2 anti-apoptotic protein (Guo et al, 2016). Another recent study reported that formononetin at 1–6 μM stimulated proliferation of estrogen receptor alpha (ERα)-positive breast cancer cell lines (MCF-7 and BT474) but did not affect the proliferation of ERα-negative breast cancer cell (MDA-MB-231) (Chen et al, 2018a).…”
Section: Anticancer Effects Of Formononetinmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated that low concentrations of formononetin (< 0.3 μM) were capable of stimulating cell proliferation and inhibiting cell apoptosis in CNE2 cells by up-regulating bcl-2 and p-ERK1/2 expression [ 21 ]. This suggests that formononetin is potentially involved in an ER-MAPK/ERK-bcl-2 signaling pathway that promotes growth.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites isolated from natural products encompassing terpenes, alkaloids, isoflavones, and polyphenols have been reported as anticancer agents [64, 65]. Anticancer properties of formononetin have been documented against several types of cancer [66] such as breast [67], colon [41], glioma [54], osteosarcoma [68], multiple myeloma [52], adrenal medulla [51], nasopharyngeal [50], prostate [49], bladder [45], laryngeal [23], lung [43], and cervical cancer [42] (Figure 3).…”
Section: Biological Activities Of Formononetin and Mechanisms Of Imentioning
confidence: 99%